Impact of Covid-19 on Food Safety: Food Security in West Africa (CEDEAO) - Seidi, Dembael (PT. Data Jaringan Visual Indonesia (Djava), 2025)
The aim of this study is to study policy decisions adopted by countries in the West African region (ECOWAS) to mitigate the effects of COVID-19 on food supply. This article was carried out using an exploratory research method using qualitative data from bibliographic and documentary sources. Information was extracted from the Food and Agriculture Policy Decision Analysis(FAPDA), which describes policy decisions taken to mitigate effects on food security. After studying these data in relation to the Global Food Security Index (GFSI) indicators, it was found that political deliberations were focused on food access and availability. In terms of access to food, policies for transforming food into cash and policies for social protection measures standout. In terms of food availability, macroeconomic policies and policies to support food production stand out. The implications of COVID-19 increase the risk of food insecurity, especially in subSaharan African regions.